Reduced levels of proteasome products in a mouse striatal cell model of huntington's disease - Dasgupta, Sayani; Fishman, Michael A.; Mahallati, Hana; Castro, Leandro M. [UNESP]; Tashima, Alexandre K.; Ferro, Emer S.; Fricker, Lloyd D. (Public Library of Science (PLoS), 2015)
Huntington's disease is the result of a long polyglutamine tract in the gene encoding huntingtin protein, which in turn causes a large number of cellular changes and ultimately results in neurodegeneration of striatal neurons. Although many theories have been proposed, the precise mechanism by which the polyglutamine expansion causes cellular changes is not certain. Some evidence supports the hypothesis that the long polyglutamine tract inhibits the proteasome, a multiprotein complex involved in protein degradation. However, other studies report normal proteasome function in cells expressing long polyglutamine tracts. The controversy may be due to the methods used to examine proteasome activity in each of the previous studies. In the present study, we measured proteasome function by examining levels of endogenous peptides that are products of proteasome cleavage. Peptide levels were compared among mouse striatal cell lines expressing either 7 glutamines (STHdhQ7/Q7) or 111 glutamines in the huntingtin protein, either heterozygous (STHdhQ7/Q111) or homozygous (STHdhQ111/Q111). Both of the cell lines expressing huntingtin with 111 glutamines showed a large reduction in nearly all of the peptides detected in the cells, relative to levels of these peptides in cells homozygous for 7 glutamines. Treatment of STHdhQ7/Q7 cells with proteasome inhibitors epoxomicin or bortezomib also caused a large reduction in most of these peptides, suggesting that they are products of proteasome-mediated cleavage of cellular proteins. Taken together, these results support the hypothesis that proteasome function is impaired by the expression of huntingtin protein containing long polyglutamine tracts.